Correction to: Exhaled nitric oxide is not a biomarker for idiopathic pulmonary arterial hypertension or for treatment efficacy - Majid Malekmohammad (BMC Pulmonary Medicine, 2019)
Following publication of the original article [1], the authors flagged that name of the author ‘Batoul Khoundabi’ had been provided with an incorrect spelling: ‘Batoutl’ was given in place of ‘Batoul’.